An Innovative Strategy for Development Children's Literacy with Canva - Lestari, Dwi; Wardani, Junita Dwi (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to explore and describe innovative strategies implemented through the digital media platform Canva and to understand its role in improving children's motivation and literacy skills.Methodology: This study employed a qualitative method with a case study approach. Data were collected through direct observation, in-depth interviews with teachers and principals, and analysis of documentation of learning media developed using Canva.Results: The study showed that the use of Canva media significantly increased children's interest and literacy skills. Interactive digital media and engaging visuals can strengthen children's understanding of symbols and words, while simultaneously encouraging children's literacy skills in learning to read and write. Teachers' active involvement in managing this media can also strengthen the effectiveness of comprehensive and sustainable literacy learning. These findings emphasize the importance of integrating interactive digital media in early childhood literacy development.